THE INFLUENCE OF LEARNING MOTIVATION AND LEARNING ENVIRONMENT QUALITY ON ACADEMIC ACHIEVEMENT OF GEN Z STUDENTS - Marina Asriyati Purnama; Tutik Winarsih (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The advancement of information and communication technology in the globalization era has significantly transformed higher education, especially in adapting to Generation Z students who are highly familiar with digital technology. These students require interactive, technology-based learning approaches, as conventional methods often fail to sustain their concentration and motivation. This study investigates the impact of two key factors learning motivation and the quality of the learning environment on academic performance. Conducted on 145 Generation Z students from the Management Study Program at STIE YAPAN Surabaya (2nd, 4th, and 6th semester), this research employs a quantitative approach using multiple regression analysis. The sampling technique used is a census, with data collected through primary questionnaires. Findings indicate that both learning motivation and the quality of the learning environment have a positive and significant effect on students' academic achievement. In other words, academic success relies on both internal drive and external support, especially for Generation Z, who are highly responsive to their surroundings. These factors work together to enhance learning outcomes.